Box A contains four equal-sized tickets, numbered 1, 2, 3 ,4
Box B contains three tickets of the same size, numbered 4, 5, 6
An experiment consists of selecting one ticket from the box A and then selecting one ticket from box B.

My answer:

sample space = {(1,4),(1,5),(1,6),(2,4),(2,5),(2,6),(3,4),(3,5),(3,6),(4,4)(4,5),(4,6)}
events where sum is at least 7 = (1,6),(2,5),(2,6),(3,4),(3,5),(3,6),(4,4),(4,5),(4,6)}

there for probability = # of possibilities meet the constraint / # of posibilities in sample space

Please advice if there is a formula to get the same answer?


#of possibilities in sample space = #tickets in A * #tickets in B (here $4\cdot 3=12$)

#of possibilities meet the constraint: Sum over thee cases of chosen tickets in Box :

for (x,6) all 4 tickets in Box A meets the conditions. For (x,5) on less -> 3, for (x,4) one more less ->2. The sum is 4+3+2=9.

Hope this Hint can help you to generalize your solution for arbitrary big boxes A and B.

| cite | improve this answer | |
  • $\begingroup$ curious if you agree with my own generalization for consecutive integers below? I think it will be harder and require more manual checking for non-consecutive integers in the sets ('boxes'). $\endgroup$ – snulty Jul 25 '14 at 18:53

Ok, you've accepted an answer. Here's a generalization for consecutive integers in the two sets.

$A=\{n,\ldots,n+m\}$, $\quad B=\{k,\ldots,k+l\}$, $n,k>0$ and $m,l\geq0$.

Let's say you want them to sum to the greater than the number $d \in \Bbb N$.

Suppose you know the least $a \in \Bbb N,\; 0\leq a \leq m$ s.t. there exists a $b \in \Bbb N, \; 0\leq b \leq l$ with $n+a+k+b\geq d$. We again choose the least of the available $b$'s.

So there are $l-b+1$ numbers $(\text{i.e. } k+b,\ldots, k+l)$ which also can be added to $n+a$.

There are $l-b+2$ numbers $(\text{i.e. } k+b-1,\ldots, k+l)$ which also can be added to $n+a+1$. and so on.

We sum these up, but there are two cases,

  1. $b\geq m-a$ and
  2. $m-a>b$

for 1). it's $\sum\limits_{i=0}^{m-a} (l-b+1)+i\quad $ numbers

and for 2). $\left(\sum\limits_{i=0}^{b} (l-b+1)+i\right) + (m-a-b)\cdot(l+1)$

We can evaluate these to be:

  1. $(m-a+1)\cdot(l-b+1)+\frac{1}{2}(m-a)\cdot(m-a+1)$
  2. $(b+1)\cdot(l-b+1)+\frac{1}{2}b\cdot(b+1)+(m-a-b)\cdot(l+1)$

Then the probability is just one of them divided by $\mid A\mid \cdot \mid B \mid$.


your one: $A=\{1,2,3,4\}$ and $B=\{4,5,6\}$

$d=7, \; m=3, \; a=0, l=2,\; b=2, \;$

using formula 2). since $m-a=3>2=b$:

$(2+1)\cdot(2-2+1)+\frac{1}{2}2\cdot(2+1)+(3-0-2)\cdot(2+1)$ which is $3+3+3=9$.

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.